Shear strength of a compacted residual soil from consolidated drained and constant water content triaxial tests - Leong, Eng Choon (2011)
Rainfall-induced landslides in unsaturated residual soils can occur slowly under drained conditions or rapidly under undrained conditions. Consolidated drained (CD) and constant water content (CW) tests have been performed to simulate the stress paths followed by soil elements in a slope that fails under drained and undrained conditions. The study was carried out to investigate the shear strength characteristics of soils associated with rainfall-induced slope failures. The soil tested was residual soil from the Jurong sedimentary formation and was reconstituted using static compaction. The test results indicate that the shear strength of the compacted specimens obtained from the CW tests agrees well with the shear strength obtained from the CD tests for the specimens with initial matric suctions less than their air-entry values. The shear strength results from the CD and CW triaxial tests start to differ when the matric suction exceeds the air-entry value of the soil. The CD and CW triaxial tests also indicate that the compacted specimens behave as a normally consolidated soil at matric suctions below the air-entry value of the soil and as an overconsolidated soil at matric suctions above the air-entry value of the soil. Results of the CW triaxial tests show that the relationship between the response of pore-water pressure and the total volume change of the specimen is more complicated than that found in the saturated undrained triaxial tests. In other words, the change in pore-water pressure during shearing is not directly related to the overall volume change of the specimen.